Paradigmatic perspectives of a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide in Namibia - Sumpi, Ndempavali; Amukugo, Hans Justus (International Journal of Health, 2016)
The aim this paper is to discuss the paradigm perspective used in a developing a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide. A study of this nature requires a paradigmatic perspective; this is a collection of logically linked concepts and propositions that provide a theoretical perspective or orientation that tends to guide the research approach to a specific topic.A paradigmatic perspective as a â€œway of looking at natural phenomena that encompasses [sic] a set of philosophical assumptions, and [sic] that guides the researcherâ€™s approach to inquiryâ€. It represents a worldview that defines for its holder, the nature of the "world," the individual's place in it, and the range of possible relationships to that world and its parts have, which include cosmological and theological points of view. Polit and Hungler (2006) describe assumptions as basic principles that are accepted as true on the basis of logic or reasoning, but without proof or verification.The paradigmatic perspective in this study consisted assumptions and the retries . These assumptions include the meta-theoretical, ontological, epistemological, axiological, and methodological assumptions. The meta theoretical basis of the study are Dickoff, James and Wiedenbachâ€™s (1968) practice theory; Kolbâ€™s experiential learning theory and Knowlesâ€™ andragogical learning theory.